Contributions of perceived parental warmth, self-esteem, and sex differences to early adolescent depression. - Lim, Hui Jun (2011)
Depression is ranked as the fourth most immobilizing illness in the world and even in Malaysia. In the literature, the contribution of parenting, self-esteem and sex on depression has been well established. Yet, the simultaneous contribution of perceived parental warmth, self-esteem and sex on depression remains unclear. Thus, the purpose of the present study is to examine the concurrent contributions of perceived parental warmth, self-esteem and sex on depression among early adolescents. The specific objectives of the study were four folds; (1) to determine sex differences in depression among early adolescents, (2) to determine the relationships between perceived parental warmth, self-esteem and depression among early adolescents, (3) to examine the direct and indirect effects of perceived parental warmth and self-esteem on depression among early adolescents, and (4) to determine the contribution of sex on the indirect effect of perceived parental warmth on depression through self-esteem among early adolescents. This quantitative study adopted a cross-sectional design using survey method , in which the sample was a subsample of a nation-wide study on parenting and adolescent’s well being.A total of 1394 participants from the study who were Form 1 and Form 2 students reported living with their married and biological parents completed the three measures; Supportive parenting scale, Rosenberg self esteem scale and Beck depression inventory for Malays. Result from the independent samples t-test indicated that sex difference exists in depression, in which females were more vulnerable to experience depression compared to males. In addition, the Pearson product moment correlation result revealed that perceived parental warmth, self-esteem and depression were correlated, in which perceived parental warmth was positively related to self-esteem while perceived parental warmth and self-esteem were negatively related to depression. Consequently, result from path analysis indicated that perceived parental warmth and self-esteem contributed to depression, in which perceived parental warmth directly and indirectly affected depression, while self-esteem directly affected depression. Furthermore, sex was found to influence the contributions of perceived parental warmth and self-esteem on depression, in which the indirect effect of perceived parental warmth to depression through self-esteem was stronger for males. Therefore, findings from the study; (1) affirms the notion by Beck that self-esteem is a core factor of depression, (2) expands the examination of parenting by two individuals (father and mother), (3) provides additional insights on the integrated contributions of perceived parental warmth, self-esteem and sex on depression, and (4) asserts the importance of self-development and parental warmth. In other words, as individuals, parents, organizations, counselors and government work together towards a common goal, the preventive measures for depression from being an epidemic among the future younger generation can be accomplished.